Are the Mean Platelet Volume and Neutrophil/Lymphocyte Ratio Predictive for Gestational Cholestasis? - Eroglu, Hasan; Tolunay, Harun Egemen; Sarsmaz, Kemal; Orgul, Gokcen; Sahin, Dilek; Yucel, Aykan (Gynecology Obstetrics & Reproductive Medicine, 2021)
OBJECTIVES: We aimed to determine whether mean platelet volume value and/or neutrophil/lymphocyte ratio values are useful as a predictive marker for gestational cholestasis. STUDY DESIGN: Retrospective analysis of the data of patients diagnosed with pregnancy cholestasis between 2018-2019 in a perinatology clinic. 352 pregnant women were enrolled in the study (122 pregnant women with Intrahepatic cholestasis as study group and 230 pregnant women with no morbidity as the control group) RESULTS: Mean platelet volume was significantly higher in pregnant women with intrahepatic cholestasis compared to the healthy controls, 9.30 (7-18) and 8.6 (6.7-11.5), respectively. The neutrophil/lymphocyte ratio was significantly higher in pregnant women with intrahepatic cholestasis compared to the healthy controls, 3.93 (0.46-13.75) and 4.25 (0.87-17.1), respectively. There was a statistically significant difference between the two groups for mean platelet volume (p <0.001). In the roc analysis, 8.85 fL for mean platelet volume had a sensitivity of 65% and a specificity of 59%. CONCLUSION: When compared with healthy pregnancies, mean platelet volume value in gestational cholestasis increases significantly. However, the predictive strength of mean platelet volume for cholestasis is not strong enough to recommend its usage as a single parameter in clinical practice.